THE REVIEW OF "TRANSLINGUAL WORDS. AN EAST ASIAN LEXICAL ENCOUNTER WITH ENGLISH" BY JIEUN KIAER, 2019. ROUTLEDGE LONDON AND NEW YORK, ISBN: 978-1-351-10947-5, pp. 160 - WOJTASIK-DZIEKAN, Emilia (International Journal of Korean Humanities and Social Sciences, 2020)
THE REVIEW OF "TRANSLINGUAL WORDS. AN EAST ASIAN LEXICAL ENCOUNTER WITH ENGLISH" BY JIEUN KIAER, 2019. ROUTLEDGE LONDON AND NEW YORK, ISBN: 978-1-351-10947-5, pp. 160.